RANCANGAN PEMANCAR PENDETEKSI FOREIGN OBJECT DEBRIS (FOD) MENGGUNAKAN SINAR LASER UNTUK MEMANTAU KEBERADAAN FOD DI BANDAR UDARA SAM RATULANGI MANADO - Hamestuti Hanggana Raras ,; Ika Endrawijaya,; Sukarwoto, (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Monitoring the presence of FOD in the air operation area of Sam Ratulangi Airport in Manado is still done manually or visually and is not carried out continuously, so that the presence of FOD is not detected directly. This can reduce time efficiency which increases the possibility of FOD damaging certain parts of the aircraft, which are feared to have an impact on flight safety. This design is used to simplify the detection of FOD carried out by general engineering officers so that the presence of FOD can be known as early as possible to be immediately removed or cleaned. The design concept of this equipment is to scan the runway surface by utilizing a laser beam and light sensor in the form of an LDR to detect the presence of FOD automatically and continuously. The FOD detection transmitter using a laser beam can detect objects in the runway area. The FOD detector transmits the object data and the position where the object is located, allowing the officer to know the existence of the FOD directly for immediate cleaning.